Scientific Temper among Junior High School Students of Balasore District, Odisha - Amulya Kumar Acharya; Shishir Mohanty (Randwick International of Education and Linguistics Science Journal, 2022)
Scientific temper is an essential skill of 21st century youth. The New Education Policy (NEP 2020) in its recommendation clearly mentioned Specific skills and abilities, such as scientific temper, creativity, communication, fitness and wellness, teamwork, problem-solving, digital literacy, ethics, and so on, will be emphasized in school. In this context each and every individual should process scientific temper for holistic development. Recently it was conducted to find out the scientific temper of high school students in relation to their gender and locality. The current study used a descriptive survey method. The sample for the present study consisted of 112 students of 10th standard studying in government schools of Sadar block and Remuna block of Balasore District of Odisha were got as the example through stratified random sampling method. Data was collected by using scientific temper test constructed by Elizabeth Joshua of Mahatma Gandhi University Kottayam. Statistical techniques like Mean, Median, S.D. and t-test to examine the data. The results of the study stated that Girls have high level of Scientific Temper compared to that of Boys, and students studying in school urban area are having high level of Scientific Temper compared to the students studying in rural area.